STUDENTS TRANSLATION OF ENGLISH TEXT INTO INDONESIAN TEXT AT THE FIFTH SEMESTER OF KHAIRUN UNIVERSITY - Mirna Bueke; Samsudin Hj Adam; Suratman Dahlan (Universitas Khairun, 2023)
This study aims to find out: (1) students' difficulties in translating English texts into Indonesian and (2) the causes of difficulties in translating texts at the fifth Semester students of English Language Education Study Program of Khairun University. This study applies a qualitative descriptive method and in analyzing data using content analysis. This study involved 12 participants. The research instrument used a test in the form of a literary text entitled